THE PHENOMENON OF JOB HOPPING AMONG GENERATION Z: AN EXPLORATION THROUGH GROUNDED THEORY - Rinta Agustiani Dwiputri; Rizki Agung Ramadani; Tiyanda Hanti Arum Kusuma; Jerry Heikal (Ikatan Dosen Menulis, 2024)
Recently, the phenomenon of job hopping has become a hot topic in Human Resource Management. It refers to the tendency of individuals, especially Generation Z, to frequently switch from one job to another in a short period of time. A survey reported that 83% of 1,100 Gen Z respondents considered themselves